PENGUKURAN KINERJA TEKNOLOGI INFORMASI PERUSAHAAN ABC MENGGUNAKAN IT BALANCED SCORECARD DAN BTRIPPLEE FRAMEWORK - Handoko Handoko; Catherine Catherine; Riche Riche (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
Information technology (IT) applied by the company can help increase the effectiveness and efficiency associated with the company's operational activities. Measurement of IT implementation is carried out on ABC companies engaged in information technology services in every business process. To integrate business processes with the current implementation of information technology, IT measurements are needed through the concept of the Balanced Scorecard (BSC) in ABC companies. In ABC companies, IT performance measurement is very important to know the extent of the company's business development stage so that it can achieve the organization's vision and mission in the short and long term. In terms of effectiveness and efficiency, ABC companies have information technology and prioritize meeting business and IT strategies. A number of business transactions carried out every day can run the risk of failure of IT implementation which impacts on the company's progress. The method used to measure IT maturity in ABC company is IT BSC combined with BTripleE Framework. From the results of the analysis conducted, there are various findings related to the risk and failure of IT implementation in the company so that an evaluation of IT is obtained which is used as a responsive action towards the IT implementation. After that, the description of the BTripleE Framework form is applied in the use of IT BSC that considers 4 perspectives through the calculation of Key Performance Indicators (KPI), including corporate contribution, future orientation, operational excellence, and customer orientation.Keywords: IT Performance Measurement, IT Balanced Scorecard, BtrippleE Framework, Key Performance Indicator